Preliminary Study of The Structure of Hesperidin and Neohesperidin as a Potential Inhibitor of SARS-CoV-2 by using The DFT Method - Sulisti, Wahyu; Sahiroh, Samakhatus; Rohman, Lutfi; Arkundato, Artoto; Wibawa, Wibawa (Jurnal Fisika, 2023)
The discovery of drugs as COVID-19 antivirals has been intensively carried out by researchers as an effort to reduce the number of victims of the COVID-19 pandemic in 2020. The discovery of main protease (Mpro) which plays a role in protein replication and transcription helped researchers identify virus inhibitors. This research has examined the potency of the bioflavonoid compounds hesperidin and the flavanon glycosides neohesperidin and their structural stability as potential inhibitors of SARS-CoV-2 by DFT computation. The first method used is the calculation of density functional theory (DFT) on hesperidin and neohesperidin molecules to optimize the geometry of the molecular structure, analysis of frontier molecular orbitals (FMO), chemical reactivity index, and map electrostatic potential (MEP).